Sistem Gesture Accelerometer dengan Metode Fast Dynamic Time Warping (FastDTW) - Chaerul Haviana, Sam Farisa (JSINBIS (Jurnal Sistem Informasi Bisnis), 2015)
In the modern environment, the interaction between humans and computers require a more natural form of interaction. Therefore, it is important to be able to build a system that can meet these demands, such as by building a hand gesture recognition system or gesture to create a more natural form of interaction. This study aims to design a smartphoneâ€™s accelerometer gesture system as human computer interaction interfaces using FastDTW (Fast Dynamic Time Warping).The result of this study is form of gesture interaction which implemented in a system that can make the process of recognition of the human hand movements based on a smartphone accelerometer which generates a command to run the media player application functions as a case study. FastDTW as the development of Dynamic Time Warping method (DTW) is able to compute faster than DTW and have an accuracy approaching DTW. From the test results, FastDTW show a fairly high degree of accuracy reached 86% and showed a better computing speed compared to DTWÂ Â